Microglia, rather than bacterial factors, mediate bovine neutrophil chemotaxis in neurolisteriosis - S. Bagatella; N. Haghayegh Jahromi; C. Monney; M. Polidori; F.M. Gall; F. Serra; R. Riedl; B. Engelhardt; A. Oevermann (Journal of Comparative Pathology, 2023)

Off-label use of dexmedetomidine in paediatric anaesthesiology: an international survey of 791 (paediatric) anaesthesiologists - Camille E. van Hoorn; Robert B. Flint; Justin Skowno; Paul Davies; Thomas Engelhardt; Kirk Lalwani; Olutoyin Olutoye; Erwin Ista; Jurgen C. de Graaff (European Journal of Clinical Pharmacology, 2021)
Purpose The purpose of this international study was to investigate prescribing practices of dexmedetomidine by paediatric anaesthesiologists. Methods We performed an online survey on the prescription rate of dexmedetomidine, route of administration and dosage, adverse drug reactions, education on the drug and overall experience. Members of specialist paediatric anaesthesia societies of Europe (ESPA), New Zealand and Australia (SPANZA), Great Britain and Ireland (APAGBI) and the USA (SPA) were consulted. Responses were collected in July and August 2019. Results Data from 791 responders (17% of 5171 invitees) were included in the analyses. Dexmedetomidine was prescribed by 70% of the respondents (ESPA 53%; SPANZA 69%; APAGBI 34% and SPA 96%), mostly for procedural sedation (68%), premedication (46%) and/or ICU sedation (46%). Seventy-three percent had access to local or national protocols, although lack of education was the main reason cited by 26% of the respondents not to prescribe dexmedetomidine. The main difference in dexmedetomidine use concerned the age of patients (SPA primarily < 1 year, others primarily > 1 year). The dosage varied widely ranging from 0.2–5 μg kg −1 for nasal premedication, 0.2–8 μg kg −1 for nasal procedural sedation and 0–4 μg kg −1 intravenously as adjuvant for anaesthesia. Only ESPA members (61%) had noted an adverse drug reaction, namely bradycardia. Conclusion The majority of anaesthesiologists use dexmedetomidine in paediatrics for premedication, procedural sedation, ICU sedation and anaesthesia, despite the off-label use and sparse evidence. The large intercontinental differences in prescribing dexmedetomidine call for consensus and worldwide education on the optimal use in paediatric practice.

Timing of risk reducing mastectomy in breast cancer patients carrying a BRCA1/2 mutation: retrospective data from the Dutch HEBON study - M. R. Wevers; M. K. Schmidt; E. G. Engelhardt; S. Verhoef; M. J. Hooning; M. Kriege; C. Seynaeve; M. Collée; C. J. van Asperen; R. A. E. M. Tollenaar; L. B. Koppert; A. J. Witkamp; et al. (Familial Cancer, 2015)

Evaluation of pedotransfer functions for estimating soil hydraulic properties of prevalent soils in a catchment of the Bavarian Alps - Christine Stumpp; S. Engelhardt; M. Hofmann; B. Huwe (European Journal of Forest Research, 2009)

Defective jejunal and colonic salt absorption and alteredNa+/H+ exchanger 3 (NHE3) activity in NHE regulatory factor 1 (NHERF1) adaptor protein-deficient mice - N. Broere; M. Chen; A. Cinar; A. K. Singh; J. Hillesheim; B. Riederer; M. Lünnemann; I. Rottinghaus; A. Krabbenhöft; R. Engelhardt; B. Rausch; E. J. Weinman; et al. (Pflügers Archiv - European Journal of Physiology, 2009)

Rare actinomycete bacteria from the shallow water sediments of the Trondheim fjord, Norway: isolation, diversity and biological activity - Harald Bredholdt; Olga A. Galatenko; Kerstin Engelhardt; Espen Fjærvik; Larissa P. Terekhova; Sergey B. Zotchev (Environmental Microbiology, 2007)
Summary Actinomycete bacteria produce a wide variety of secondary metabolites with diverse biological activities, some of which have been developed for human medicine. Rare actinomycetes are promising sources in search for new drugs, and their potential for producing biologically active molecules is poorly studied. In this work, we have investigated the diversity of actinomycetes in the shallow water sediments of the Trondheim fjord (Norway). Due to the use of different selective isolation methods, an unexpected variety of actinomycete genera was isolated. Although the predominant genera were clearly Streptomyces and Micromonospora, representatives of Actinocorallia , Actinomadura , Knoellia , Glycomyces , Nocardia , Nocardiopsis , Nonomuraea , Pseudonocardia , Rhodococcus and Streptosporangium genera were isolated as well. To our knowledge, this is the first report describing isolation of Knoellia and Glycomyces species from the marine environment. 35 selected actinomycete isolates were characterized by 16S rDNA sequencing, and were shown to represent strains from 11 different genera. In addition, these isolates were tested for antimicrobial activity and the presence of polyketide synthase and non‐ribosomal peptide synthetase genes. This study confirms the significant biodiversity of actinobacteria in the Norwegian marine habitats, and their potential for producing biologically active compounds.

Aggregations of juvenile whale sharks (Rhincodon typus) in the Gulf of Tadjoura, Djibouti - D. Rowat; M. G. Meekan; U. Engelhardt; B. Pardigon; M. Vely (Environmental Biology of Fishes, 2007)

Accidental intrathecal infusion of cefotiam: clinical presentation and management - G. Brssner; K. Engelhardt; R. Beer; B. Pfausler; A. Georgopoulos; E. Schmutzhard (European Journal of Clinical Pharmacology, 2004)

Astrocyte mediated modulation of blood-brain barrier permeability does not correlate with a loss of tight junction proteins from the cellular contacts - Stefan Hamm; Bndicte Dehouck; Jrg Kraus; Karen Wolburg-Buchholz; Hartwig Wolburg; Werner Risau; Romo Cecchelli; Britta Engelhardt; Marie-Pierre Dehouck (Cell and Tissue Research, 2004)

Brain Abscess due to Capnocytophaga Species, Actinomyces Species, and Streptococcus intermedius in a Patient with Cyanotic Congenital Heart Disease - K. Engelhardt; A. Kampfl; M. Spiegel; B. Pfausler; H. Hausdorfer; E. Schmutzhard (European Journal of Clinical Microbiology & Infectious Diseases, 2002)

ISOLATION AND MOLECULAR CHARACTERIZATION OF BRAIN MICROVASCULAR ENDOTHELIAL CELLS FROM HUMAN BRAIN TUMORS - RONALD E. UNGER; JENS B. OLTROGGE; HAGEN VON BRIESEN; BRITTA ENGELHARDT; ULRIKE WOELKI; WOLFGANG SCHLOTE; RÜDIGER LORENZ; HANSJÜRGEN BRATZKE; C. JAMES KIRKPATRICK (In Vitro Cellular & Developmental Biology - Animal, 2002)

Insulin responsiveness of sheep, ponies, miniature pigs and camels: results of hyperinsulinemic clamps using porcine insulin - Kaske M.; Elmahdi B.; Engelhardt W.; Sallmann H.-P. (Journal of Comparative Physiology B, 2001)

Ultrastructural localization of adhesion molecules in the healthy - Karen Wolburg; Holger Gerhardt; Martina Schulz; Hartwig Wolburg; B. Engelhardt (Cell and Tissue Research, 1999)

Immunohistochemical localization of the murine transferrin receptor (TfR) on blood-tissue barriers using a novel anti-TfR monoclonal antibody - K. Kissel; S. Hamm; Martina Schulz; Annunciata Vecchi; Cecilia Garlanda; B. Engelhardt (Histochemistry and Cell Biology, 1998)